Diseño de manual de identidad corporativa para el posicionamiento estratégico - González, Ericka D. (2019)
This study aims to determine the feasibility of creating the image and identity along with a corporate identity manual as tool for the Imbabura Student Sports Federation (FDEI), located in Ibarra city, with 32 years of foundation being parents of great sporting talents at provincial and national level. In Chapter I, the theoretical framework was developed and based on criteria and investigations of different bibliographical authors consulted on the web, articles and books to achieve the research structure as an objective to the realization of the project. In chapter II the methodology was carried out that was applied, thanks to it, we were able to obtain pure or basic information with the aim to improve it, the population was identified and a technique of survey was did to obtain information on the questions given by indicators, it gave the results with its correct tabulation and analysis, concluding that project development is feasible because it will help positively to the FDEI, where the lack of knowledge about the image and identity of the FDEI and the management of a corporate manual was eliminated , being this a strategy to position in the minds of consumers, in the Chapter III We will announce how the Corporate Identity Manual is created, construction process of imago type, sizes, incorrect uses, typography, color, application of funds, basic stationery, uniforms, online system production, signage among others; financing economic and human resources invested in this project are also disclosed.